Differences in perceived sources of uncertainty in natural hazards science advice: lessons for cross-disciplinary communication - Doyle, Emma E. H.; Thompson, Jessica; Hill, Stephen R.; Williams, Matt; Paton, Douglas; Harrison, Sara E.; Bostrom, Ann; Becker, Julia S. (Frontiers in Communication, 2024)
We conducted 31 mental model interviews in Aotearoa NZ to understand perspectives of uncertainty associated with natural hazards science. Participants included hazard scientists (n=11, e.g., geophysical, social, and other sciences), professionals with some scientific training (n=10, e.g., planners, policy analysts, emergency managers), and lay public participants with no advanced training in science (n=10, e.g., journalism, history, administration, art, or other domains). Such natural hazards science contains many layers of interacting uncertainties, and varied understandings about what these are and where they come from creates communication challenges, impacting the trust in and use of science. To improve effective communication, it is thus crucial to understand the many diverse perspectives of uncertainty. Here we present a comparative analysis of the mental model maps produced by participants, considering individuals' levels of training and expertise in, and experience of, science. A qualitative comparison identified increasing map organization with science literacy, suggesting greater science training, expertise, or experience with science results in a more organized and structured mental model of uncertainty. There were also language differences, with lay public participants focused more on perceptions of control and safety, while scientists focused on formal models of risk and likelihood. These findings are presented to enhance hazard, risk, and science communication, alongside the design of our interview methodology, which could be adapted for participatory and co-development research.